2016
DOI: 10.1016/j.bbadis.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Novel miR-5582-5p functions as a tumor suppressor by inducing apoptosis and cell cycle arrest in cancer cells through direct targeting of GAB1, SHC1, and CDK2

Abstract: MicroRNAs (miRNAs) play pivotal roles in tumorigenesis as either tumor suppressors or oncogenes. In the present study, we discovered and demonstrated the tumor suppressive function of a novel miRNA miR-5582-5p. miR-5582-5p induced apoptosis and cell cycle arrest in cancer cells, but not in normal cells. GAB1, SHC1, and CDK2 were identified as direct targets of miR-5582-5p. Knockdown of GAB1/SHC1 or CDK2 phenocopied the apoptotic or cell cycle arrest-inducing function of miR-5582-5p, respectively. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…[ 72 ] In recent years, studies have shown that miRNAs regulate cell proliferation, cell migration, and angiogenesis in colorectal cancer by targeting Src. [ 73 75 ] In this study, miR-141 significantly reduced in serum exosomes of colorectal cancer and Src was predicted as a target gene of miR-141. Therefore, we speculated that miR-141 may play a role as a tumor suppressor via targeting Src gene in CRC.…”
Section: Discussionmentioning
confidence: 74%
“…[ 72 ] In recent years, studies have shown that miRNAs regulate cell proliferation, cell migration, and angiogenesis in colorectal cancer by targeting Src. [ 73 75 ] In this study, miR-141 significantly reduced in serum exosomes of colorectal cancer and Src was predicted as a target gene of miR-141. Therefore, we speculated that miR-141 may play a role as a tumor suppressor via targeting Src gene in CRC.…”
Section: Discussionmentioning
confidence: 74%
“…The protein expression level of CD31 has been detected to be decreased in the BPD group (Wang et al 2014), a finding of which was similar to ours: the positive expression rate of CD31 protein displayed a notable decline in lung tissues of neonatal mice with hyperoxia-induced BPD. miR-29b leads to retarded growth of intestinal epithelial cells and suppressing GAB1 expression induces apoptosis (An et al 2016). In addition, decreased miR-29a-3p expression gives rise to enhanced proliferation of glioma cells via the upregulation of GAB1 (Shao et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of these oncogenic signalings is important for CRC cell progression [1,8,9]. Recent studies have focused on expression and potential functions of Gab1, the most dominant Gab family protein, in CRC [10,28,29]. It has been shown that Gab1 is over-expressed and/or over-activated in CRC, which is associated with cancer cell progression [10,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on expression and potential functions of Gab1, the most dominant Gab family protein, in CRC [10,28,29]. It has been shown that Gab1 is over-expressed and/or over-activated in CRC, which is associated with cancer cell progression [10,28,29]. For example, An et al, showed that miR-5582-5p selectively degrades Gab1 to inhibit CRC cells [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation